2018
DOI: 10.1002/cctc.201801072
|View full text |Cite
|
Sign up to set email alerts
|

Mechanism of the Dinuclear Iron Enzyme p‐Aminobenzoate N‐oxygenase from Density Functional Calculations

Abstract: AurF is a diiron enzyme that utilizes two dioxygen molecules as the oxidant to catalyze the oxidation of p‐aminobenzoate to p‐nitrobenzoate. Density functional calculations were performed to elucidate the reaction mechanism of this enzyme. Two different models were considered, with the oxygenated intermediate being a diferric peroxo species or a diferric hydroperoxo species. The calculations strongly favor the model with a diferric peroxo species and support the mechanism proposed by Bollinger and co‐workers. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
12
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(15 citation statements)
references
References 99 publications
3
12
0
Order By: Relevance
“…Such butterfly-like structure of P1 is analogous to those proposed in sMMO, 5,94 epoxidase BoxB, 25,50 ToMo, 51,95 CmlA, 52 and AurF. 49 For the end-on binding Z-like P2, its energy is 1.8 kcal/mol higher than that of P1. In the case in which Asp315 is bidentate-coordinated to both irons, the corresponding energy of P3 is 3.8 kcal/mol higher than that of P1.…”
Section: Possible Structures Of P In Sznfsupporting
confidence: 63%
See 2 more Smart Citations
“…Such butterfly-like structure of P1 is analogous to those proposed in sMMO, 5,94 epoxidase BoxB, 25,50 ToMo, 51,95 CmlA, 52 and AurF. 49 For the end-on binding Z-like P2, its energy is 1.8 kcal/mol higher than that of P1. In the case in which Asp315 is bidentate-coordinated to both irons, the corresponding energy of P3 is 3.8 kcal/mol higher than that of P1.…”
Section: Possible Structures Of P In Sznfsupporting
confidence: 63%
“…However, the subsequent work by Liao and co-workers presented an alternative mechanism for AurF. 49 Based on the DFT model calculations, it was found that N-oxygenation by the P intermediate is kinetically favored over that via the protonated P. 49 In spite of all of the aforementioned mechanistic insights, the structure and the reactivity of the peroxo-Fe 2 (III/III) intermediate in SznF are still elusive. Scheme 1 shows the putative mechanisms for the reactions of the peroxo-Fe 2 (III/ III) intermediate that emerge from previous investigations of SznF.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…For the concerted mechanism, the O−O bond cleavage and the electrophilic attack on the toluene substrate take place, affording a cationic tetrahedral σ ‐complex Int1 with barriers of 16.8 kcal/mol for both ortho and meta attacks. This mechanism avoids the formation of the high‐valent diferryl Q species, and this strategy has also been applied in BoxB [11a] and AurF [8f,15b,17] . Unlike BoxB, which favors the formation of epoxide products, [11b] ToMOH is reluctant to undergo epoxide formation due to the formation of a stable arenium cation intermediate.…”
Section: Discussionmentioning
confidence: 99%
“…In this work, based on the recently obtained crystal structure of PtmU3 in complex with the substrate, a series of computational models with different coordination modes of dioxygen as well as different reactive species (Fe2 III –superoxo or Fe2 IV –oxo) to trigger the H-abstraction have been constructed, and the successive C5 β-hydroxylation by the diiron center has been explored by using the QM/MM approach, which has been widely applied in exploring the catalytic mechanism of enzymes, including some diiron-containing enzymes. ,, …”
Section: Introductionmentioning
confidence: 99%